Impact of Training & Development (T&D) on Employee’s Performance & Productivity (P&P) - Saleh, Mohammad Yusuf; Azimi, Hamdullah (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study explores the critical impact of Training and Development (T&D) on improving employees' Performance and Productivity (P&P), specifically within the context of JACK NGO in Parwan, Afghanistan. In a competitive global environment, corporate entities and non-governmental organizations must ensure their workforce possesses relevant and contemporary skills. Employing a quantitative research methodology, this study utilizes linear regression analysis to assess data gathered from a sample of 275 participants through a rigorously structured questionnaire. Additionally, secondary data sources were used to support the findings, which reveal a strong and statistically significant positive relationship between T&D initiatives and enhancements in employee performance and productivity (P&P) at JACK NGO. Notably, on-the-job training is a particularly effective facet of T&D, directly contributing to enhanced employee outcomes. This research underscores the necessity of strategically optimizing T&D programs as a fundamental strategy for bolstering employee effectiveness and driving organizational success at JACK NGO. The results suggest the need for strategic investments in extensive training programs, which improve employee skills and support the organization’s broader goals and vision, ultimately fostering sustainable growth and a positive impact within the community it serves.